2022
DOI: 10.1002/smj.3405
|View full text |Cite
|
Sign up to set email alerts
|

Birds of a feather flock (even more) together: An intergroup relations perspective on how #MeToo‐related media coverage affects the evaluation of prospective corporate directors

Abstract: This study examines how incumbent director reactions to media coverage of the #MeToo movement have impacted the evaluation of prospective corporate directors. We argue that heightened intergroup anxiety related to male-female interactions leads incumbents to seize on social attributes that bolster category-based trust in the reliability of prospective directors' interpersonal behavior. We predict that in response to #MeToo coverage, incumbents evaluate board candidates more positively when they share demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…The in-group favoritism explains why employee representative directors may strategically decide to maximize the stakeholder (the employee) benefits in the boardroom (Adams et al, 2011). In the nominating committee of a multi-ethnic board, out-group salience is evident when Malay or Chinese members of the nominating committee form the majority, leading to a reduction in board diversity and affect their board tasks (Pirzada et al, 2017), and concern about the #MeToo movement triggers stress among nominating committee members, leading them to recommend potential new board members with similar demographic characteristics (Bednar et al, 2022). For outside directors who identified themselves as the in-group members with the majority usually end-up being a conformist, decreasing the monitoring role and are likely to be reappointed (Yoo & Koh, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in-group favoritism explains why employee representative directors may strategically decide to maximize the stakeholder (the employee) benefits in the boardroom (Adams et al, 2011). In the nominating committee of a multi-ethnic board, out-group salience is evident when Malay or Chinese members of the nominating committee form the majority, leading to a reduction in board diversity and affect their board tasks (Pirzada et al, 2017), and concern about the #MeToo movement triggers stress among nominating committee members, leading them to recommend potential new board members with similar demographic characteristics (Bednar et al, 2022). For outside directors who identified themselves as the in-group members with the majority usually end-up being a conformist, decreasing the monitoring role and are likely to be reappointed (Yoo & Koh, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Cannella et al (2015) also found that both directors (the family-founder and lone-founder) strategically appoint external directors with similar experiences and serve longer to maintain their sense of belonging to the firms and prevent their untrustworthiness. Similarly, ORID’s strength helps to appoint new board members with similar demographics to ensure no issues arise related to the #MeToo movement to protect the organization’s image (Bednar et al, 2022). The result is in tandem with the proposition that the stronger the ORID, the higher the directors value the organizations’ essence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, our paper contributes to strategy process research aiming to understand how the media (e.g., Bednar et al, 2022), analysts (e.g., Benner & Ranganathan, 2012), and other stakeholders (e.g., Li et al, 2022) shape strategy formation. While organizations frequently seek out positive coverage (Westphal et al, 2012), our work suggests that organizational hubris is a potential dark side of public adulation that can have long‐lasting implications.…”
Section: Discussionmentioning
confidence: 99%
“…Although many governance researchers have studied the antecedents of demographic diversity in the boardroom, including organizational predictors (Hillman, Shropshire, and Cannella, 2007) and industry peer pressure (Knippen, Shen, and Zhu, 2019), we know little about whether local events at the community level can impact boardroom diversity and corporate governance. Of particular relevance, a recent study by Bednar, Westphal, and McDonald (2022) found that media coverage of the #MeToo social movement can influence how incumbent directors evaluate prospective director candidates. In addition, McDonnell and Cobb (2020) found that social activism directly targeting firms can prompt the departure of directors who hold similar values as those of the activists.…”
Section: Discussionmentioning
confidence: 99%